A teia de Simão Roiz : inquisição e sociabilidades na capitania da Bahia - Mattos, Andreza Silva (2014)
On Tuesday January 19, 1593, after the concluded case of his inquisitorial process, the soldier frontiersman Simon Roiz was imprisoned in the jail of the city of Salvador. Years before, he had left his home in the land of ingenuity Sergipe do Conde (Recôncavo baiano) and he was to the hinterland of the Bahia Province to rescue Gentiles space where found freedom, the loophole that allowed him to take actions that were against Catholic dogmas - Christian was on the coast and in the hinterland gentle, a man with hybrid cultural behaviors. From the sociability of Simon Roiz group, we take as the object of this research the socio-cultural relations between frontiersmen soldiers, Jesuits and Indians in the occupation of northern hinterland Captaincy of Bahia, in the late sixteenth century process. The time frame covers the period between 1590 and 1595, moments in which, respectively, Roiz Simon joined the hinterland and the General Council of the Inquisition was positioned about the sentence he implied. Taking as sources inquisitorial procedures, work from the perspective of cultural history, situating the analysis in the thematic field of |history of beliefs: roundness and cultural hybridity.| In this direction, we use the resources of the Italian micro-history, understood here as an approach that will enable us to know the past through various signs, signals and possibilities.